Stress aggravates and prolongs imiquimod‐induced psoriasis‐like epidermal hyperplasis and IL‐1β/IL‐23p40 production. Issue 1 (18th May 2020) - Wang, Yan; Li, Ping; Zhang, Lu; Fu, Jing; Di, Tingting; Li, Ningfei; Meng, Yujiao; Guo, Jianning; Zhao, Jingxia
Abstract: Psoriasis is a common, chronic multifactorial inflammatory skin disease with both genetic and environmental components. A number of studies have suggested that psoriasis episodes are often preceded by stressful life events. Nevertheless, the underline mechanisms of stress in psoriasis remain unexplored. To address this question, we established an emotional stress mouse model induced by empty bottle stimulation, and applied imiquimod (IMQ), a ligand of TLR7/8 and effective potent immune activator, on the dorsal skin to induce psoriasis‐like lesions. We found that empty bottles induced emotional stress exaggerated and prolonged psoriasiform dermatitis, which appeared as more prominent epidermal hyperplasia in the emotional stress mice compared with the control mice. Higher mRNA expression of Il‐1β, Il‐17a, and Il‐22, as well as higher secretion of IL‐1β, IL‐12p40, IL‐17, and IL‐22 were observed in the skin lesion of emotional stress mice. The emotional stress condition and IMQ treatment synergistically led to higher expression levels of neurotransmitters and their receptors in the skin, especially substance P (SP), we also found that SP could stimulate DCs to secrete more IL‐23p40 in vitro. In addition, NK‐1R antagonist partially abrogated enhanced epidermal thickness and the level of neurotransmitters in emotional stress mice. Taken together, these results indicate that stress exacerbates and prolongs psoriasiform dermatitis in mice by up‐regulating IL‐1β and IL‐23p40, which were related to local DCs stimulated by abnormal SP. Abstract : Emotional stress aggravated and prolonged psoriasiform dermatitis in a mouse model by upregulating IL‐1Î² and Il‐23p40, which were related to local DCs activation stimulated by abnormal SP; provides new insight into neuro‐immunotherapy in psoriasis treatment.